Perspectives on common variable immune deficiency - Park, Joon H. (2011)
Common variable immunodeficiency (CVID) is considered to be a collection of genetic immune defects with complex inheritance patterns. While the main phenotype is loss of B cell function, the majority of the genetic mechanisms leading to CVID remain elusive. In the past two decades there have been increasing efforts to unravel the genetic defects in CVID. Here, we provide an overview of our current understanding of the genetic basis of these defects, as revealed over time by earlier linkage studies in large cohorts, analysis of families with recessive inheritance, targeted gene approaches, and genome-wide association studies using single nucleotide polymorphism arrays and copy number variation, and whole genome studies.